PELAKSANAAN PEMBANGUNAN PERUMAHAN DENGAN POLA PEMBERDAYAAN MASYARAKAT DI KOTA PEKANBARU TAHUN 2013 - Deni Hariandi; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Based on Law No. 39 of 1999 on Human Rights stated that decent housing is a basic right of citizen of Indonesia. Currently in Pekanbaru has a number of houses uninhabitable reach 2120 homes. So the Pekanbaru city government to implement a development program simple house habitable conducted with the pattern of community empowerment.This study aims to determine how the implementation and factors - factors that affect the implementation of the housing development with the pattern of community empowerment in Pekanbaru 2013. This study used a qualitative descriptive approach using purposive sampling method with data collection using interviews, observation, and documentation.Results of this research is the implementation of the Housing Development Patterns Community Empowerment in Pekanbaru City in 2013 has not been entirely successful. Factors - factors that affect, among others: Standards and Objectives, Resources, Communication and Implementation Attitudes and Social, Economic and Political.Keywords: Implementation, Home Livable, Community Empowerment